Peningkatan Kemampuan Berpikir Kritis Siswa Kelas V SD 5 Bulungcangkring Menggunakan Model Problem Based Learning Berbantuan Media Question Card - Damayanti, Miftakhunnisa; ., Khamdun; Masfuah, Siti (WASIS : Jurnal Ilmiah Pendidikan, 2024)
The purpose of this study was to analyze the average difference between the pretest and posttest scores of students before and after learning using the Problem Based Learning model assisted by Question Card media on critical thinking skills of grade V students of SD 5 Bulungcangkring; to measure the increase in students' critical thinking skills in the IPAS subject matter of grade V students of SD 5 Bulungcangkring by using the Problem Based Learning model assisted by Question Card media. This research was conducted using the Quantitative Experiment method with the One-Group Pretest-Posttest Design type. The subjects in this study were all fifth grade students of SD 5 Bulungcangkring, totaling 20 students using a non-probability sampling technique of saturated sample type. Data collection used were observation, interviews, tests and documentation. Data analysis in this study used expert judgment validity test, t-test and n-gain test. The results of this study indicate testing of the paird sample t-test shows the Sig (2-tailed) value of 0.001 0.05, then Ho is rejected Ha is accepted, so there is a difference in the average pretest value of 59.9 while the average posttest value is 89.7. With the percentage of the N-Gain value getting 76.5% which indicates an effective interpretation.